Predictors of antisocial attitudes and doping intentions in sport: The role of coach interpersonal style and athletes` psychological needs - Ntoumanis, N.; Barkoukis, V.; Gucciardi, D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Our statistical review of the literature (Ntoumanis et al., 2014) showed that relatively little research on doping in sport has examined the contributing role of social environments. Recent research (e.g., Bartholomew et al., 2011) has utilized the self-determination theory framework (Deci & Ryan, 2002) to show how adaptive and maladaptive coach motivational strategies predict a number of indices of athlete psychological and physical functioning (e.g., disordered eating, burnout, depression). However, it is unknown how coach adaptive and maladaptive motivational strategies relate to athletes` intention and engagement in doping behavior. Hence, our study draws from self-determination theory to address this gap in the literature. Methods: Data collection took place in Australia and Greece at the beginning of the sport season. In Australia 211 athletes (140 males) from a variety of sports completed the survey (Mage = 22.69 years; SDage= 5.721). In Greece 237 athletes (146 males) provided responses (Mage = 21.99 years; SD= 3.9). The majority of athletes were competing at a state or national level. Athletes completed a questionnaire pack containing a number of validated questionnaires. All procedures were carried out in accordance with APA ethics guidelines. Results: Structural equation modeling analysis provided support for a model in which perceptions of autonomy supportive coaching environment positively predicted athletes` perceptions of psychological need satisfaction. Controlling coach environments were predictors of experiences of thwarted/frustrated needs. Thwarted needs were positive predictors of moral disengagement, antisocial attitudes and intention to dope. The opposite pattern of results was observed for need satisfaction and these outcomes. A number of country differences in these findings emerged. Discussion: Results from this study can inform interventions that aim to provide coach anti-doping education from a self-determination perspective, in terms of creating optimal coaching environments that support athletes` psychological needs.